A Comparative Study of Epistemological Foundations of the "Fundamental Reform Document of Iran Education System" and Rhizomatic Approach - Mahbobe Janbozorgi; Hamid Reza Rezazadeh Bahadoran; Abbas Gholtash; Alireza Araghieh (Comparative Education Society of Iran ( CESIR), 2021)
The purpose of study was a comparative study of the epistemological foundations of the "Fundamental Reform Document of Iran Education System" and the epistemological foundations of the rhizomatic approach. The research method was comparatively qualitative and research population includes all related resources such as books and journals. Method of data collection and analysis were documentary and content analysis respectively. Findings reveal similarities between two epistemological foundations in different aspect of cognition such as goals (dynamics of science), domain (rationalities), method (acquired science), source (experience) and tool (senses and desire). The main differences between the epistemological foundations of the Fundamental Reform Document of Iran Education System and rhizomatic approach are in goals of cognition (Human-centered, reasoning and becoming), domain of cognition (effects), nature of cognition (existential / non-organic oriented), method of cognition (presence science/ confronted-oriented science), source of cognition (revelation, intellect, communication) and tool of cognition (inspiration , intuition, heavenly book / network). It is suggested that in the process of revising "Fundamental Reform Document of Iran Education System", the epistemological foundations of the rhizomatic approach should be considered by Iranian educational policy makers